An investigation of the molecular properties of 1,1,1-trichloro methyl silane using laser spectroscopy - Pelle, Makungwane Branda (North-West University, 2008)
Silicon carbide (SiC) is formed from methyltrichlorosilane (CH3SiCI3) during a chemical vapour deposition process [Osterhold et al., 1994]. Silicon carbide is one of the important compounds for the Pebble Bed Modular Reactor (PBMR) process because it is used as a coating film in the kernel of the fuel cell. For the current chemical vapor deposition process at the PBMR to be improved, the process of the formation of silicon carbide layer from methyltrichlorosilane must be fully understood. Molecular mechanics, semi empirical, Hatree-Fock and Moller-Plesset modelling calculations were performed using the Spartan modelling program to obtain information about the molecular structure and properties of the CH3SiCl3 molecule. The electron densities, energy profiles for rotation as well as the infrared spectra were calculated using different (MMFF, DFT, 3-21G and STO-3G) basis sets. The results were confirmed by obtaining experimental UV/V is absorption spectroscopy, FT-IR and Raman spectroscopy. The nanosecond and fem to second laser activation and ionization technique was used to ionize methyltrichlorosilane molecules at 795 nm and 397.5 nm of the fem to second laser. Nanosecond lasers used include the Nd:YAG laser at 266 nm, as well as a tunable dye laser at 212.5 nm. Product formation was analyzed using the time of flight mass spectrometry technique. The main difference between the nanosecond and fem to second laser ionization is the detection of the parent ion CH3SiCl3+ in the fem to second mass spectra while in the nanosecond mass spectra it was not observed. The effect of experimental parameters (laser energy, laser focusing) in the time of flight spectrometer on ionization (peak signal) were investigated. The results obtained in this study demonstrate that by increasing laser energy the ion peak signal also increases. Also, the delay time between the laser pulse and the gas pulse had to be set appropriately to give the optimum signal which was found to be between 400 and 900 µs for the nanosecond laser and 0.6 to 2 ms for the fem to second laser. The results showed that the best focusing position of the laser beam, using a lens to adjust the focus that gives optimum peak intensities, is between 0 and 1 mm for both the nanosecond and the fem to second lasers.
Thesis (M.Sc. (Chemistry))--North-West University, Potchefstroom Campus, 2009.